Cystic fibrosis and COVID-19: Care considerations - Mirza, Alicia A. (Respir Med Case Rep, 2020)
The coronavirus disease 2019 (COVID-19) pandemic has demanded large scale changes in patient care. People with cystic fibrosis have unique considerations, including underlying lung disease and routine aerosolizing therapies, but there is insufficient evidence to create comprehensive practice guidelines. We share a case of a patient with CF and COVID-19 as well as alterations to routine CF care at a large academic center. Key considerations include accessible COVID-19 screening, augmented infection control practices, and rapid integration of telemedicine.